KEJADIAN PNEUMONIA PADA BATITA DI WILAYAH KERJA PUSKESMAS SUKAMERINDUKOTA BENGKULU - Hartini, Lela (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
Pneumonia is an infection or inflammation of the lower respiratory tract thatinvolves the alveoli and bronchioles. Risk factors for pneumonia which occurs in boysaged 1-3 years with a skinny body weight. Pneumonia is the leading cause of death ofinfants and toddlers in Indonesia with a total percentage (23.6%), which is the largestproportion of all-cause mortality in infants and toddlers. In the city of Bengkulu numberof events in 2014 pneumonia were 942 (6.07%), Sukamerindu health centre is first orderwith 51 people, Basuki Rahmat 47 people, and 39 people in Lingkar Barat. Purpose ofthis study was to determine the incidence of pneumonia in toddlers picture in PuskesmasSukamerindu in 2014. This study used a descriptive design, with a population of childrenaged 1-3 years which amounted to 51 people, technique data sampling was used TotalSampling, data collection secondary techniques, data obtained by existing records inhealth centers (patient registers). The results showed that the majority (60.8%) childrenaged 13-24 months, the majority (72.5%) child-sex male, and most (56.9%) children werein the category of lean body weight. It is recommended to parents, especially mothers tobe able to take precautions against the occurrence of pneumonia, such as providingadequate nutrition to children so that children are not malnourished which can increasethe risk of pneumonia